-(5x-4)+3x-6=-2

Simple and best practice solution for -(5x-4)+3x-6=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-4)+3x-6=-2 equation:


Simplifying
-1(5x + -4) + 3x + -6 = -2

Reorder the terms:
-1(-4 + 5x) + 3x + -6 = -2
(-4 * -1 + 5x * -1) + 3x + -6 = -2
(4 + -5x) + 3x + -6 = -2

Reorder the terms:
4 + -6 + -5x + 3x = -2

Combine like terms: 4 + -6 = -2
-2 + -5x + 3x = -2

Combine like terms: -5x + 3x = -2x
-2 + -2x = -2

Add '2' to each side of the equation.
-2 + 2 + -2x = -2 + 2

Combine like terms: -2 + 2 = 0
0 + -2x = -2 + 2
-2x = -2 + 2

Combine like terms: -2 + 2 = 0
-2x = 0

Solving
-2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-2'.
x = 0

Simplifying
x = 0

See similar equations:

| 6r+4r=70 | | (3x+6)+(2x-1)+90=180 | | 7(d-9)=7 | | -5=5/7n | | w^2(w+7)=18 | | 36x^2+30x-36=6x-4 | | 6x-(3x+6)=15 | | 11p+6=2(p-6) | | 5/7*56 | | 8x-2=5x-68 | | (b+3)(b+5)=0 | | 3ay/2ay | | 40x=323.07 | | w-2=O | | -11y+6x=260 | | 6x-11y=-260 | | 8(6c-1)-8=46c+8 | | 6(a-10)=12 | | 260+6x=11y | | 4n-3=35 | | 5a+2b=0 | | 8x+2(1.5x)=84.61 | | 8x+2(1.5x)=96.15 | | 10t-16=44 | | 8x+2(1.5x)=88.46 | | -7x+9y=24 | | 8x+2(1.5x)=126.92 | | 100=1+9d | | 2x+15=2x-3 | | 18x^2+7x-72=0 | | 8x+2(1.5x)=61.53 | | 8-3/4x=1/2x |

Equations solver categories